2017
DOI: 10.13005/ojc/330334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of A New Stability Indicating Method for the Determination of Aceclofenac and Thiocolchicoside in Pharmaceutical Dosage form By RP-HPLC.

Abstract: A new RP-HPLC method was developed and validated for the estimation of aceclofenac and thiocolchicoside in their tablet dosage form. The chromatographic separation was carried out by using Agilent Zorbax column (150 × 4.6mm, 5µm). The mobile phase containing the combination of methanol and 0.1% ortho phosphoric acid of 75:25 (v/v) ratios. In this method the flow rate used is 1 min/ml for the separation at the detection wavelength of 275 nm. The proposed method was validated according to the ICH guidelines. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…However, with the recent evidence of development of aneuploidy, the European Medicines Agency's Committee on Human Medicinal Products has recommended that the authorized uses for thiocolchicoside containing medicines for use by mouth or injection should be restricted. [29], [31].s…”
Section: Introduction 11 Etodolacmentioning
confidence: 99%
“…However, with the recent evidence of development of aneuploidy, the European Medicines Agency's Committee on Human Medicinal Products has recommended that the authorized uses for thiocolchicoside containing medicines for use by mouth or injection should be restricted. [29], [31].s…”
Section: Introduction 11 Etodolacmentioning
confidence: 99%
“…The anti-inflammatory properties are comparable to other NSAIDs Through literature survey on the analysis of aceclofenac indicated that it can be analyzed in bulk or combination by various analytical techniques like titrimetric, 16 colourimetric, 17 spectroflurimetric, 17 densitometric, 18 HPLC, [19][20][21][22] HPTLC, 23 spectrophotometric [24][25][26] and stripping voltametric.. 27 From the literature reports, it is profound that the RP-HPLC stability indicating methods are mainly for the simultaneous analysis of aceclofenac in pharmaceutical dosage forms. [19][20][21][22][28][29][30][31][32][33]…”
Section: Introductionmentioning
confidence: 99%